Investigation of Cryptosporidium spp. Antigen By ELISA in Stool Specimens Sent to Our Laboratory between 2010 and 2018 - Yunus Emre Beyhan; Hasan Yılmaz (Türkiye Parazitoloji Dergisi, 2020)

(untitled)
Objective:Cryptosporidium is an enteric protozoan parasite that affects human and many animal species in worldwide. Staining methods or stool antigen detecting methods are using for detection of Cryptosporidium in faeces. It is known that the ELISA method has high sensitivity and specificity in practice. The aim of this study is to demonstrate the frequency of this parasite by ELISA in samples sent to our laboratory between 2010 January and 2018 September.Methods:The study was conducted on a total of 723 patients, 431 men and 292 women, who were referred to the Parasitology Laboratory from various outpatient clinics due to digestive system complaints. The presence of Cryptosporidium spp. antigen was investigated by ELISA method.Results:Cryptosporidium spp. was not found in any patient with Nativ-lugol method, whereas Cryptosporidium spp. antigen positivity was detected in 2.8% of 723 patients. In the study, 2.5% of the males and 3.1% of the females were found positive in terms of having the parasite, and there was no significant difference in gender between the parasite frequencies. The highest rate of parasite positivity (4.5%) was found in the 0-6 age group.Conclusion:The high rate of cryptosporidiosis detected in our study is thought to be related to factors such as widespread animal husbandry in our region, poor hygiene rules and low socio-economic level. As a result of considering the findings of our study, evaluation of patients with intestinal complaints in terms of Cryptosporidium will be useful for accurate diagnosis, regardless of whether they have diarrhea and/or they are immunocompromised.